2007
DOI: 10.1002/elps.200700093
|View full text |Cite
|
Sign up to set email alerts
|

Scanning copy number and gene expression on the 18q21‐qter chromosomal region by the systematic multiplex PCR and reverse transcription‐PCR methods

Abstract: We examined differences in copy number and expression of 127 genes located on the 18q21-qter chromosomal region of the breast and prostate cancer cell lines, using the systematic multiplex PCR and reverse transcription-PCR (SM PCR and SM RT-PCR) methods that we developed. Semi-quantitative data were obtained that were comparable in quality, but not in quantity, to data from DNA microarray hybridization analysis. In the chromosomal region where losses are frequent in breast, prostate, and other cancers, we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…As earlier reported in primary breast cancers (Yamamoto and Yamamoto, 2007), we found that CCBE1 expression was downregulated in the majority of ovarian cancer cell lines tested and in primary ovarian carcinomas as compared with NOSE. Loss of CCBE1 expression was significantly associated with higher grade ovarian carcinomas and likely occurs early in ovarian carcinogenesis, with stage I carcinomas expressing lower levels of CCBE1 than NOSE, one predicted cellular origin of ovarian carcinomas.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As earlier reported in primary breast cancers (Yamamoto and Yamamoto, 2007), we found that CCBE1 expression was downregulated in the majority of ovarian cancer cell lines tested and in primary ovarian carcinomas as compared with NOSE. Loss of CCBE1 expression was significantly associated with higher grade ovarian carcinomas and likely occurs early in ovarian carcinogenesis, with stage I carcinomas expressing lower levels of CCBE1 than NOSE, one predicted cellular origin of ovarian carcinomas.…”
Section: Discussionsupporting
confidence: 86%
“…Collagen and calcium-binding EGF domains 1 (CCBE1) is an earlier uncharacterised gene of unknown function that has recently been reported to be down-regulated in primary breast carcinomas as compared with matched normal breast tissue (Yamamoto and Yamamoto, 2007). CCBE1 maps to 18q21.32, a common region of loss of heterozygosity (LOH) in ovarian cancer (Takakura et al, 1999;Lambros et al, 2005) that is associated with malignant progression of ovarian cancer (Hauptmann et al, 2002) and high tumour grade and poor survival (Lassus et al, 2001).…”
mentioning
confidence: 99%
“…The full ORF of RNF152 has been sequenced and confirmed by the Mammalian Gene Collection program (Strausberg et al, 2002). Decreased expression of RNF152 was reported in some cancer cell lines (Yamamoto and Yamamoto, 2007). Our studies showed for the first time that RNF152 is an E3 ligase and is self-polyubiqutinated.…”
Section: Introductionsupporting
confidence: 65%
“…Human RNF152 gene is located on 18q21.33 chromosomal region (Yamamoto and Yamamoto, 2007) and encodes a 203-amino-acid protein with predicted molecular weight of 22 kDa. RNF152 protein contains two predicted functional domains: a RING finger motif at N-terminus, with the sequence resembling a canonical RING motif (CX 2 CX 14 CX 1 HX 2 CX 2 CX 12 CX 2 C), and a transmembrane motif at the C-terminus (Fig.…”
Section: Rnf152 Is a Highly Conserved Ring Finger Proteinmentioning
confidence: 99%
“…Furthermore, the upregulated expression of transcription factor ONECUT2 was revealed in breast and prostate cancer cell lines (32), and increased IFI16 protein in normal human prostate epithelial cells was associated with cellular senescence-associated cell growth arrest (33). NEUROG3 was identified to be expressed in metastatic neuroendocrine prostate cancer cells (34).…”
Section: Discussionmentioning
confidence: 99%